Membangun Innovative Work Behavior di Era Digital: Kompetensi Digital, Agility Karyawan, dan Lingkungan Kerja Digital - Rossitika, Amanda Rizky; Istikhoroh, Siti; Harjanti, Dhyah; Sitepu, Rismawati Br; Noerchoidah (Jurnal Ilmu Manajemen, 2026)
This study aims to analyze the effect of digital competence on employee agility and innovative work behavior, as well as the mediating role of employee agility and the moderating role of the digital work environment among employees in the creative graphic design industry in East Java. This study uses a quantitative method. Data collection was conducted using an online questionnaire via Google Forms. The sample was determined using purposive sampling. A total of 180 questionnaires were collected and analyzed using PLS-SEM in SmartPLS. This study found that digital competence has a positive and significant impact on employee agility and innovative work behavior. In addition, employee agility was found to mediate the relationship between digital competence and innovative work behavior, indicating that agility plays an important role in creating innovative work behavior. This study also found that the digital work environment moderates the relationship between digital competence and employee agility, highlighting the importance of a technology-supportive work environment to improve work effectiveness. These findings contribute to Dynamic Capability Theory, emphasizing that digital competence and employee agility function as dynamic capabilities that drive organizational innovation and competitiveness. Practical and research implications are discussed.